CORONARY HEART DISEASE AND OSTEOPOROSIS IN POSTMENOPAUSAL WOMEN - Khusainova Munira Alisherovna; Makhmudova Khanuza Davranovna; Khaydarova Zarrina Erkinovna (Journals Park Publishing, 2024)
Osteoporosis is a disease affecting connective tissues. The spine is most often affected, as well as the bones of the arms and legs. Bones in osteoporosis lose their strength, which leads to the risk of frequent pathological fractures. The development of osteoporosis is due to the amount of accumulated bone tissue and the degree of subsequent decrease in bone mass. However, these reasons are determined by a number of other factors. This disease is so urgent that the World Health Organization has named osteoporosis the fourth cause of morbidity and mortality from chronic non-communicable diseases. The purpose of the study. To study the main clinical features of the manifestation of a combination of coronary heart disease and OP in postmenopausal women. Materials and methods. 110 menopausal women with concomitant diseases (CHD and OP) and 20 practically healthy women were examined as controls. The degree of manifestation of menopausal syndrome was calculated by the Kupperman menopausal index according to the modification of E.V. Uvarova. Research results and their discussion. At the first stage of the study, all women were divided into groups depending on the menopause period. Conclusions: 1. When identifying the main clinical manifestations of coronary heart disease and osteoporosis in women, an epidanamnesis is a very important point, which makes it possible to determine the severity of the menopausal syndrome. 2. In menopausal women, the main clinical manifestations of menopausal syndrome, coronary heart disease and osteoporosis directly correlate with the period of menopause development, severity and degree of its severity.
Keywords: coronary heart disease, osteoporos, menopausal syndrome.